Прогнозирование долговечности деталей пс эт методом акустической эмиссии - Зубенко, Денис Юрійович (Eastern-European Journal of Enterprise Technologies, 2011)
Is has been found that their longevity is determined by the local stress state of the material associated with the parameters of AE at a fixed voltage, as well as its stiffness is determined by features of AE characteristics